On the Shoulders of Giants - Barr, Earl; Bird, Christian; Hyatt, Eric; Menzies, Tim; Robles, Gregorio (FSE/SDP Workshop on the Future of Software Engineering Research, 2010)
Science rests on peer review and the wide-spread dissemination of knowledge. Software engineering research will advance further and faster if the sharing of data and tools were easier and more wide-spread. Pragmatic concerns hinder the realization of this ideal: the time and effort required and the risk of being scooped. We examine the costs and benefits of facilitating sharing in our field in an effort to help the community understand what problems exist and find a solution. We examine how other fields, such as medicine and physics, handle sharing, describe the value of sharing for replication and innovation, and address practical concerns such as standards and warehousing. To launch what we hope will become an ongoing discussion of solutions in our community, we present some ways forward that mitigate the risk of sharing — partial sharing, registry, escrow, and market.